The Effect of Warm Water Foot Soaking Therapy and Hand Massage on Blood Pressure and Anxiety in Hypertensive Patients - Takumasang, Reza Resaldi; Iswanti, Dwi Indah; Widiyaningsih, Widiyaningsih; Gero, Sabina (Universitas Tanjungpura, 2025)
Background: Hypertension is a widely recognized cardiovascular disease where patients' blood pressure rises above normal levels. Hypertension is also known as a